Effectiveness of mindfulness-based cognitive therapy among depressed individuals with disabilities in Nigeria: A randomized controlled trial - Musa, Zulkiflu Argungu; Soh, Kim Lam; Mukhtar, Firdaus; Soh, Kwong Yan; Oladele, Tajudeen Olalekan; Soh, Kim Geok (Elsevier, 2021)
The objective of this paper was to examine the efficacy of mindfulness-based cognitive therapy (MBCT) in decreasing depressive symptoms and intellectual disabilities (ID) among individuals with depression in Nigeria. In this randomized controlled trial, 101 participants with depression and ID, aged 18-60 years, who obtained 14 scores in the Beck Depression Inventory (BDI-II), scores 4 and above on Shaheen Disability Scale (SDS), were randomly assigned into the interventions (n = 50) and active control group (n = 51). The MBCT group has shown a statistically significant effect on the SDS and BDI-II variables by decreasing depressive symptoms and disabilities following MBCT (p<0.05). The assessment revealed that participants reported an improvement in their experience of depression and ID. The most significant impact was in the reduced levels of ID reported. The results of the evaluation suggest that depressed people with intellectual disabilities benefit from a structured MBCT group intervention and the results are maintained at 2-months follow-up.